Optimizing the Role of Digital Marketing as a Promotional Media for MSMEs in Tajungan Village: Array - Agung Adriansyah; Hafidz Nurhuda; Umi Novita Fauziyah (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2022)
In this digital era, the MSME sector has a very vital role in economic growth and development in Indonesia. The MSME sector should be able to adapt to the times, especially in terms of marketing products using digital media. Community Service Partners in this activity are Micro, Small and Medium Enterprises (MSMEs) in Tajungan Village, Kamal District, Bangkalan Regency which are engaged in the business of production and buying and selling. However, the marketing activities are still very simple. For this reason, MSMEs need to be given training on the importance of using digital marketing so that their marketing system can be better so that they can expand their business targets. This community service program aims to provide knowledge in promotion, innovation and development strategies related to optimizing business marketing media. The purpose of this activity is to maximize marketing or sales that will have an impact on the economy of the community in general. The results of the implementation of this activity include increased knowledge and understanding of MSME actors regarding digital marketing as a promotional media, the use of online platforms such as the Canva, Shopee, and Facebook Marketplace applications as marketing media instruments has also increased, skills in using these applications are getting better and innovations. product marketing innovations are increasingly diverse. By using a positive approach in the form of a participatory, reflective and innovative approach, MSMEs in Tambegan Village are expected to be able to adapt along with the times